THE PHILOSOPHICAL ESSENCE OF TECHNICAL AND VOCATIONAL EDUCATION AND TRAINING IN THE DIGITAL ERA: A SYSTEMATIC LITERATURE REVIEW - Saputra, Andi; Abdullah, Rijal; Giatman, M.; Mardizal, Jonni (Smart Education, 2026)
Abstract: This study aims to provide a comprehensive philosophical justification for Technical and Vocational Education and Training (TVET) by examining how ontological, epistemological, and axiological foundations can strengthen its role in the modern era. This study addresses growing concerns that TVET is increasingly dominated by a market-driven instrumental paradigm that neglects its humanistic, reflective, and ethical dimensions. A Systematic Literature Review (SLR) was conducted following the PRISMA protocol. This review synthesized 34 Scopus-indexed journal articles published between 2020 and 2025, identified through Boolean-based keyword searches focusing on philosophical, conceptual, and theoretical perspectives in TVET. The selected studies were analyzed using qualitative thematic analysis to explore the philosophical justifications and their implications for TVET. This review reveals an intense philosophical urgency in redefining TVET amid rapid digitalization, Industry 4.0 demands, social inequality, and widening skill gaps. The philosophical foundations collectively shift TVET from a mechanistic skills training model to a holistic human development system. A philosophical approach contributes to character building, work ethic, and social awareness through virtue ethics, practical wisdom (phronesis), and spiritual workability. This study presents a comprehensive philosophical framework for reevaluating the essence and direction of TVET. By integrating ontology, epistemology, and axiology, this research offers a new conceptual lens to strengthen TVET as a transformative, humanistic, and socially responsive education system. Keywords: Technical and Vocational Education and Training (TVET); Philosophy of education; Vocational knowledge; Ethical competence; Systematic Literature Review Abstrak: Penelitian ini bertujuan untuk memberikan pembenaran filosofis yang komprehensif untuk Pendidikan dan Pelatihan Teknis dan Kejuruan (TVET) dengan mengkaji bagaimana landasan ontologis, epistemologis, dan aksiologis dapat memperkuat perannya di era modern. Studi ini membahas kekhawatiran yang berkembang bahwa TVET semakin didominasi oleh paradigma instrumental yang digerakkan oleh pasar yang mengabaikan dimensi humanistik, reflektif, dan etisnya. Tinjauan Literatur Sistematis (SLR) dilakukan mengikuti protokol PRISMA. Tinjauan ini mensintesis 34 artikel jurnal terindeks Scopus yang diterbitkan antara tahun 2020 dan 2025, diidentifikasi melalui pencarian kata kunci berbasis Boolean yang berfokus pada perspektif filosofis, konseptual, dan teoretis dalam TVET. Studi yang dipilih dianalisis menggunakan analisis tematik kualitatif untuk mengeksplorasi pembenaran filosofis dan implikasinya terhadap TVET. Tinjauan ini mengungkapkan urgensi filosofis yang intens dalam mendefinisikan ulang TVET di tengah digitalisasi yang cepat, tuntutan Industri 4.0, ketidaksetaraan sosial, dan kesenjangan keterampilan yang melebar. Fondasi filosofis secara kolektif menggeser TVET dari model pelatihan keterampilan mekanistik menuju sistem pengembangan manusia yang holistik. Pendekatan filosofis berkontribusi pada pembentukan karakter, etika kerja, dan kesadaran sosial melalui etika kebajikan, kebijaksanaan praktis (phronesis), dan kemampuan kerja spiritual. Studi ini menyajikan kerangka filosofis yang komprehensif untuk mengevaluasi kembali esensi dan arah TVET. Dengan mengintegrasikan ontologi, epistemologi, dan aksiologi, penelitian ini menawarkan lensa konseptual baru untuk memperkuat TVET sebagai sistem pendidikan yang transformatif, manusiawi, dan responsif secara sosial. Kata kunci: Pendidikan dan Pelatihan Teknis dan Kejuruan (TVET), Filsafat pendidikan, Pengetahuan vokasi, Kompetensi etika, Tinjauan Literatur Sistematis